Education, Tenure, and Training on Nurse Knowledge in Handling Emergency Patients - Rasi Rahagia; Zumrotul Ula; Suprapto Suprapto (Sarana Ilmu Indonesia (Salnesia), 2026)
The knowledge and competencies of nurses critically influence the quality and safety of emergency patient care. This study aimed to analyze the relationship between education level, tenure, and participation in emergency training programs with nurses’ knowledge in handling emergency patients. An analytical observational study with a cross-sectional design was conducted among 30 nurses working in the Emergency Department of a Type C regional hospital in Indonesia. Data were collected using a structured and validated questionnaire. Bivariate analysis was performed using Fisher’s Exact Test with a significance level of α = 0.05. The findings showed that most respondents were aged 20–30 years (80%), had higher educational qualifications (53.3%), had worked for less than five years (60%), and had participated in formal emergency training (53.3%). Significant associations were identified between nurses’ knowledge and educational level (p = 0.011), tenure (p = 0.007), and emergency training participation (p = 0.014). Nurses with higher education and emergency training demonstrated better knowledge levels. Interestingly, nurses with shorter working experience showed higher knowledge, possibly due to greater exposure to updated curricula and recent emergency training. This study highlights the importance of continuous professional development, structured emergency training, and competency-based nursing education in improving emergency nursing preparedness and patient safety. Hospitals should strengthen regular certification and refresher training programs to maintain the quality of emergency healthcare services.